Confronting the barriers to develop novel vaccines against brucellosis - Oliveira, Sérgio Costa (2011)
Brucellosis is an important zoonotic disease of nearly worldwide distribution. This pathogen causes abortion in domestic animals and undulant fever, arthritis, endocarditis and meningitis in humans. Currently, there is no vaccine licensed for brucellosis in humans. Furthermore, control of brucellosis in the human population relies on the control of animal disease. Available animal vaccines may cause disease and in some cases have limited efficacy. This article discusses recent studies in the development of recombinant protein, DNA and live-attenuated vaccines against brucellosis. Furthermore, we call the attention of the scientific community, government and industry professionals to the fact that for these novel vaccine initiatives to become licensed products they need to be effective in natural hosts and bypass the regulatory barriers present in several countries. © 2011 Expert Reviews Ltd.